Economic Reforms and Factory Sector - Ganesan, S.; Anbumani, V. (Indian Journal of Marketing, 2007)
This paper presents the analytical results of growth, partial factor productivity and total factor productivity based on Solow’s index in the Tamil Nadu Factory Sector during pre (1980-81 to 1990-91) and post (1991-92 to 2001-2002) Economics reform period. Economic development of any nation depends heavily and extensively on the industrial sector. The Factory Sector in Tamil Nadu has been assigned an important role in the economic development of nation via the State. Our planners envisaged industrialization as an instrument of development policy and decentralisation of factory sector was conceived as a corrective mechanism for inter and intra regional imbalances in development. The Government of India and State Government have set up an array of institutional agencies to facilitate the growth of industries (Factory Sector) in the country. As a result, industries have not only increased but they have also generated employment opportunities and export earnings. In terms of range of goods produced and services rendered as well as variety of technology mastered by this sector, the progress has indeed been very impressive.